Creative curriculum as an alternative of change in the education system - Gómez Gallardo, Luz Marina (2014)
The goal of this article is to raise awareness about the importance of developing a creative curriculum and applyit in Regular Basic Education as well as the upper level inorder to promote an education that takes into account the diversity of personalities, rhythms and styles of learningin children and youths; the intention continues to be the same: every child and young person can improve their social and individual skills, and strengthen their knowledge. Both children and young people tell their experiences and feelings, they listen and watch carefully, and learn new concepts. For this reason, different methods of preplannedteaching can be used, in order to offer studentsa learning process that makes sense. Children and young people can work in groups and individually, this will involveall the senses and will develop themselves intellectually, emotionally and physically. They can experiment with different materials, expand and assimilate their knowledge of nature, and their skills to manipulate the media, all this in a creative way.